2013
DOI: 10.3109/15569527.2013.839997
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oral cyclosporine in the treatment of severe alopecia areata

Abstract: This study indicates that oral cyclosporine treatment may be a beneficial treatment option for severe AA. In addition to this, disease duration is an important prognostic factor that influences efficacy of oral cyclosporine treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Regarding the disease duration, all patients with durations less than 24 months had significant clinical improvement, while patients with disease duration exceeding 24 months showed no response to LD-MTX treatment. Similar to our results, other studies also have suggested that disease duration is an important prognostic factor in AA718.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding the disease duration, all patients with durations less than 24 months had significant clinical improvement, while patients with disease duration exceeding 24 months showed no response to LD-MTX treatment. Similar to our results, other studies also have suggested that disease duration is an important prognostic factor in AA718.…”
Section: Discussionsupporting
confidence: 93%
“…Conventional treatments include systemic corticosteroid and local steroid injections234. Immunomodulators such as cyclosporine and azathioprine are also used567. However, some cases of AA remain intractable or experience frequent recurrence necessitating novel treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…This point should be further investigated in prospective research. Maintenance of remission phase is the aim for clinicians and is challenging because of the recurring nature of the disease [38,39]. Gupta et al [33] reported 100% (6/6) recurrence rate of the disease after discontinuation of the CsA monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized half-head trial study including patients of recalcitrant AA treated with topical bexarotene, no difference was demonstrated between the two sides [40]. [17,[41][42][43].…”
Section: Topical Bexarotenementioning
confidence: 95%